Analisis Bahasa Slang dalam Interaksi Virtual pada Platform Game Roblox: Kajian Sosioliungistik: Analysis of Slang in Virtual Interactions on the Roblox Game Platform: A Sociolinguistic Study - Maulida, Zerlina; Pujihastuti, Etin; Riyanton, M. (Information Technology and Science(ITScience), 2025)
Advances in digital technology have changed the way teenagers communicate, particularly on online gaming platforms like Roblox. This platform has become a platform for the development of slang, a variation of informal language used for quick and efficient communication during gameplay. Slang in online games takes various forms and continues to evolve in response to changing communication needs and trends. The purpose of this study is to describe the forms of slang found in the game